The Construction of Play: Rules, Restrictions, and the Repressive Hypothesis. (September 2014) - Tulloch, Rowan
Rules are often cited as one of the defining features of games; however, few precise definitions of rules exist and those that do are often self-contradictory and/or reductive. This article seeks to reconceptualize rules for both traditional and digital games, not as a series of restrictions to which the player must submit but rather as a relationship of power that functions through the player and through processes of construction. I argue that the restrictive model of rules is embedded within the liberal humanist paradigm, where power is understood as an external force operating on the subject. Building upon poststructuralist theorizations of power, I demonstrate that rather than operating through restriction, rules construct the possibility of the game, producing the game world and norms of play practice. Through this, I show that rules should not be understood in opposition to player agency, but rather as a contributor to, and product of it.